2011
DOI: 10.3354/cr00980
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the timing of Betula pubescens budburst. I. Temperature and photoperiod: a conceptual model

Abstract: The main factors triggering and releasing bud dormancy are photoperiod and temperature. Their individual and combined effects are complex and change along a transition from a dormant to a non-dormant state. Despite the number of studies reporting the effects of temperature and photoperiod on dormancy release and budburst, information on the parameters defining these relationships is scarce. The aim of the present study was to investigate the effects and interaction of temperature and photoperiod on the rates o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
87
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(96 citation statements)
references
References 34 publications
8
87
1
Order By: Relevance
“…1). Indeed, it has been assumed since the beginning of the twentieth century that, for the majority of temperate and boreal tree species, a certain duration of chilling temperatures ranging between 0 and 5°C is responsible for the release from endodormancy (Coville 1920;Sarvas 1974;Hänninen 1990;Caffarra et al 2011b). However, the range of chilling temperatures required for an efficient release from endodormancy has not yet been clearly identified (Dantec et al 2014).…”
Section: Phenology Of Leaves and Reproductive Structuresmentioning
confidence: 99%
See 2 more Smart Citations
“…1). Indeed, it has been assumed since the beginning of the twentieth century that, for the majority of temperate and boreal tree species, a certain duration of chilling temperatures ranging between 0 and 5°C is responsible for the release from endodormancy (Coville 1920;Sarvas 1974;Hänninen 1990;Caffarra et al 2011b). However, the range of chilling temperatures required for an efficient release from endodormancy has not yet been clearly identified (Dantec et al 2014).…”
Section: Phenology Of Leaves and Reproductive Structuresmentioning
confidence: 99%
“…Recent advances suggest that this range of chilling temperature is likely to be species-specific (Laube et al 2014) and may cover a broader spectrum than commonly assumed (Harrington et al 2010). Once endodormancy is released, warm temperatures have a clear positive effect on bud development during ecodormancy, with a warmer spring leading to an earlier budburst (Sarvas 1972;Sarvas 1974;Campbell and Sugano 1975;Lang et al 1987;Caffarra et al 2011b). The influence of warm spring temperatures is particularly obvious in mountainous areas, where tree populations flush gradually later toward higher elevations (Vitasse et al 2009), with only a small fraction of the variability explained by the genetic differentiation among populations .…”
Section: Phenology Of Leaves and Reproductive Structuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Along these lines, photoperiod can cue flowering in alpine plants when snowmelt is early, thereby setting a limit to how early plants can flower [17,25]. At the same time, plants may be able to adjust their photoperiod thresholds to match local site conditions, and temperature can override photoperiod [17,26,27]. Therefore, photoperiod may not always act to limit to how early plants can flower.…”
Section: Introductionmentioning
confidence: 99%
“…At least two studies have shown that flowering phenology in a few species can exhibit a threshold or nonlinear response to the timing of spring snowmelt (sensu figure 1a; [15,23]), and plant phenology is often modelled using nonlinear temperature functions [27,34,35]. However, the prevalence of these types of long-term responses within plant communities is largely unknown.…”
Section: Introductionmentioning
confidence: 99%